Évaluation de la mise en œuvre d’un dispositif de formation d’enseignants associés au Québec par le biais d’une recherche développement - Louise M. Bélair; Isabelle Vivegnis; Josée Lafrance (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In order to synchronize the training of supervisors of student teachers in Quebec, videos and guidelines have been developed as educational devices. Using a regulation process, their relevance and consistency have been evaluated with regards to the educational themes proposed by the reference framework for the training of student teachers’ supervisors. This paper presents the results from the development research design used by the research team to ensure the validity of this educational device.